ETHNOBOTANY, PHYTOCHEMISTRY AND PHARMACOLOGY OF OCHNA SCHWEINFURTHIANA: A REVIEW - AJ, Yusuf; MI, Abdullahi; AA, Muhammad (Universal Journal of Pharmaceutical Research, 2020)
Ochna schweinfurthiana (Os, Family: Ochnaceae) is a small evergreen tree used in ethnomedicine to treat different ailments; it is also used in agri-horticulture and as ornaments, dyes among others. It is a rich source of complex dimers of flavonoids and used for treatment of pain, inflammation, and arthritis. Chemical investigations carried out on the different parts of the plant have been confined to phenolic compounds majorly, bioflavonoids, glycosides, steroids and terpenes. The plant, O. schweinfurthiana have shown a wide spectrum of biological and pharmacological properties which include antimicrobial, cytotoxic/antiproliferative, genotoxicity, antinociceptive, anti-inflammatory, antioxidant and antiplasmodial. This review comprehensively summarizes the potential effects of the plant O. schweinfurthiana, chemically and pharmacologically. However, more researches in the aspect of phytochemical and biological studies are needed to exhaustively isolate bioactive compounds and evaluate their effects on other ailments as claimed by the traditional healers. Peer Review History: Received 4 October 2019; Revised 7 November; Accepted 28 December; Available online 15 January 2020 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Mohamed Derbali , Faculty of Pharmacy, Monastir, Tunisia, mohamed.edderbali@gmail.com Ahmad Najib , Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id